Penerapan nilai islam dalam pentadbiran dan pemikiran politik Tun Dr. Mahathir (1981-2003): Suatu penilaian - Mohd Johan, Yami (2015)
Tun Dr. Mahathir was the fourth Prime Minister of Malaysia. His tenure was from 1981-2003 (22 years). Although Tun Dr. Mahathir declared Malaysia as an Islamic state, there is criticsm and opinion that is thinking and his administration did not reach the level of political Islam. This study aims to identify his views and thoughts with regards to Islam abd how he practised and applied it in his administration and its impact on the coutry‟s political climate. The study uses the qualitative method which focuses on interviews and documentations. In addition, the core areas of the study are mainly concentrated on spoken and written texts as the subunits of the analysis which later are classified in the form of narrative description. The findings show that Tun Dr. Mahathir‟s thinking was parallel with the Islamic political aspects which also blended the Islamic concepts and administrative policies. In fact, this indirect approach has put in place a proper Islam as enshrined in the Federal Constitution. Tun Dr. Mahathir also used this approach to develop the Muslims through the mastery of knowledge for enhancing the position of Malaysia as a model Islamic country. At the same time, he fought for Islam to be the country‟s main power and educate the people to adopt a holistic approach to Islam. This success was due to the ability of Tun Dr. Mahathir‟s socio-economic development to improve the life of the Muslims in Malaysia who had previously lagged behind other races. In addition, Tun Dr. Mahathir succeeded in strengthening the socio-political aspects of Islam in a comprehensive manner through the preparation and stabilization of the state bureaucracy system. Finally, the findings also show that Tun Dr. Mahathir definitely imprated Islamic concepts in his administration, however, it was not obvious. Most of the concepts were used on a practical basis through the launching of programmes in the country. In a nutshell, they suited the approaches practised by Tun Dr. Mahathir, that is fairness and moderation, considering that Malaysia is a pluralistic country